The white lady of Brandberg, South-West Africa, her companions and her guards - (:unkn) unknown (My University, 1948)
The Brandberg is a neo-granitic moutain standing on a foundation of basalt, indurated schist and quartzite, and is situated 70 miles from Cape Cross where the Portuguese ships of Diego Cam anchored in 1485. These mariners erected one of their stone crosses, making no effort to explore the interior and seeing none of the inhabitants. The Brandberg lies 250 miles by car northwest of Windhoek, the capital of South-West Africa, near the edge of the high sub-desertic plateau of meagre grass plains savannas, withe no permanent waterholes, in a region where there is gold, alluvial tin and copper. Vast Old Palaeolithic and Middle Stone Age stations lie along the base of this range in the parts where there are sheets of granitic gravels, indurated schist and white vein quartz. This shows that the present desertic onditions have not always existed. The late Middle Stone Age and Late Stone Age sites are even more frequent below the granitic rocks shelters near the temporary or seasonal waterholes, round wich there are sometimes abundant remains of Hottentot pottery.
Keywords: African Research